Multitasking while studying – grit moderates the relationship of situational motivation and multitasking - Bachmann, Olga; Grunschel, Carola; Fries, Stefan (Frontiers in Psychology, 2024)
Multitasking during studying is frequent among students. In this experience sampling study we examine if multitasking during studying can be explained by situational study motivation and the personality trait grit; and if grit moderates the relationship of situational motivation and multitasking. Eighty-eight students participated. All participants planned to write an important exam within the upcoming two weeks. Situational motivation was conceptualized along the lines of self-determination theory, differentiating between autonomous and controlled motivation. Also, we assessed students' grit. Hypotheses were tested using multilevel modelling in MPlus. As predicted, students multitasked less when situational study motivation was autonomous (vs. controlled). Contrary to predictions, we did not find a significant main effect of grit on multitasking. However, the interaction effect was significant, indicating that in situations with relatively controlled study motivation grittier students are more likely to refrain from multitasking than their less gritty peers.